Effectiveness of Cryotherapy in VIA positive women - Pradhan, Binita; Pradhan Malla, Anagha (Journal of General Practice and Emergency Medicine of Nepal, 2021)
Introduction: In this study we studied the effectiveness of Cryotherapy in cases with abnormal squamous intraepithelial lesions detected only by VIA. Method: In our study, 64 patients in reproductive age group attending gynecology OPD, with complaints of discharge per vaginum, lower abdominal pain, and post coital bleeding were screened with VIA and positive women had cryotherapy and they were followed up by same after six months. Result: A total of 64 VIA positive women had cryotherapy. Most of the women were of age group 31-40 years (40.6%). Majority of the women were of parity 2 or more (89.1%). The most common complaint was discharge (46.9%) followed by pelvic pain (32.8%). VIA was negative among most of the women (87.5%) after cryotherapy. The outcome of cryotherapy was not associated with age and parity rather presence of symptoms was statistically associated (p=0.034). Conclusion: We concluded that in low resource settings, simple and safe diagnostic test VIA and therapeutic procedure cryotherapy are safe and effective method to combat the killer disease of cervical cancer.